Indonesian Migrant Workers: A Study of International Legal Protections and Their Relevance to SDGs Point 8 - Yokhebed Arumdika Probosambodo; Josef Purwadi Setiodjati; Ayu Kumala Sari Hamidi (Indonesian Journal Publisher, 2025)
The phenomenon of Indonesian migrant workers reflects a critical nexus between labor migration, international law, and sustainable development. Indonesia is among the world’s largest labor-sending countries, with millions of its citizens employed abroad, particularly in the Middle East and Asia. Remittances from migrant workers provide substantial economic benefits for the state and households, yet these workers often face systemic vulnerabilities including exploitation, discrimination, and inadequate legal protection. This article examines the extent to which international law and Indonesia’s national legal framework safeguard the rights of migrant workers while contributing to the realization of Sustainable Development Goal (SDG) 8: Decent Work and Economic Growth. International instruments such as the 1990 International Convention on the Protection of the Rights of All Migrant Workers and their Families (ICRMW) and relevant ILO conventions provide comprehensive standards, but their effectiveness is constrained by limited ratification from key receiving states. At the domestic level, Indonesia has enacted Law No. 18 of 2017 on the Protection of Indonesian Migrant Workers (UU PPMI), which represents a shift toward state responsibility and alignment with international human rights norms. Nevertheless, implementation challenges ranging from weak enforcement and bureaucratic overlap to insufficient diplomatic support abroad remain significant. The findings suggest that while Indonesia has made normative progress, practical protection is hindered by governance gaps and lack of cooperation from host countries. Strengthening enforcement, regional collaboration, and worker empowerment are crucial to ensuring that Indonesian migrant workers achieve genuine “decent work” as envisioned by SDG 8.